ASSESSMENT OF THE RELATIONSHIP BETWEEN MARKET-BASED FINANCIAL SYSTEM AND GROSS DOMESTIC PRODUCT PAR CAPITA, KENYA. - Tenesi, Mukholi Gabriel; Chesoli, Joshua Wafula; Nyangau, Andrew Songoro (IJRDO - Journal of Business Management, 2023)
This study assessed the relationship of market-based financial system development indicators and Gross Domestic Product par capita in Kenya. for the period running from 1997 to 2007. The Gross Domestic Product was as low as 1.2% in the first macroeconomic stability in the period running from 1997 to 2001 and was as high as 7.0% in the second macroeconomic stability in the period running from 2002 to 2007. Data capture was by census technique and checking of secondary material on Kenya National Bureau of Statistics(KNBS), Nairobi Security Exchange(NSE), and Capital Market Authority(CMA), Data analysis and interpretation was through descriptive statistics and inferential statistics. The financial indicators of a market-based financial system were characterised as size, activity and efficiency indicators. Stock market capitalization/GDP, private bond market capitalization/GDP, public bond market capitalization/ GDP were size indicators. Stock market total value traded / GDP was activity indicator. Stock market turn- over ratio was efficiency indicator. This study was in relation to literature review which depicts some financial indicators as being counterproductive to each other and in their contribution to GDP per capita. In the first macroeconomic stability (1997-2001), the bank based financial system was79% against 21% of the market based financial system. In the second macroeconomic stability (2002-2007), the bank based financial system was 54% against 46% of the marked based financial system. Financial indicators (Public bond capitalization Ksh.bn/GDP, Market Capitalization Ksh.bn/GDP, turnover ratio and total value traded) as significant predictor of GDP per capita and significantly correlated to GDP par capita in Kenya.